Sleep Stewardship - Sanjay Kalra; Madhur Verma; Viny Kantroo; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Sleep stewardship is a systematic effort to ensure relaxed and restorative sleep, by optimizing pre-sleep, intra-sleep and post-sleep environment and ambience, in a rational manner. It includes not only sleep hygiene and prevention of sleeping pill abuse, but also macro- and meso-level interventions to improve sleep quality. The person living with sleep disorder, their family, members of society, health care professionals, and policy makers: all have a role to play in sleep stewardship. Sleep stewardship is necessary to improve and maintain human health Keywords: Lemborexant, obstructive sleep apnea, sedatives, sleep, sleep hygiene, tranquilizers, zolpidem.